Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0886
|View full text |Cite
|
Sign up to set email alerts
|

Search for new supernova remnant shells in the Galactic plane with H.E.S.S.

Abstract: A search for new supernova remnants (SNRs) has been conducted using TeV γ-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534−571. The TeV source is therefore classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the first scenario, the TeV emission is produced by a PWN from the energetic pulsar PSR J1913+1011; however, no X-ray emission was detected from the pulsar or its putative PWN (Chang et al 2008). The second scenario is that there is a low surface brightness SNR producing the TeV emission (see, e.g., Puehlhofer et al 2015), but no clear SNR has yet been detected (see, e.g., Su et al 2017;Reich & Sun 2019). 2CXO J191237.9 +101044 is labeled as an extended source in the CSCv2, but its 10′ off-axis location makes it difficult to differentiate between extended emission or multiple point sources, as Chandraʼs PSF degrades with increasing off-axis angle.…”
Section: Unidentified Tev Sources From the Hess Galactic Plane Surveymentioning
confidence: 99%
“…In the first scenario, the TeV emission is produced by a PWN from the energetic pulsar PSR J1913+1011; however, no X-ray emission was detected from the pulsar or its putative PWN (Chang et al 2008). The second scenario is that there is a low surface brightness SNR producing the TeV emission (see, e.g., Puehlhofer et al 2015), but no clear SNR has yet been detected (see, e.g., Su et al 2017;Reich & Sun 2019). 2CXO J191237.9 +101044 is labeled as an extended source in the CSCv2, but its 10′ off-axis location makes it difficult to differentiate between extended emission or multiple point sources, as Chandraʼs PSF degrades with increasing off-axis angle.…”
Section: Unidentified Tev Sources From the Hess Galactic Plane Surveymentioning
confidence: 99%
“…However, the identification of TeV sources as SNRs is absolutely not trivial and entirely relies on their shell-like appearance and a TeV morphology matching their shell-like counterparts in radio and non-thermal X-rays. Using the increased data set of the Galactic Plane Survey, the HESS collaboration has reported the detection and identification of one new shell-type SNR candidate [29], HESS J1534−571, is coincident with the radio SNR G323.7−1.0 recently detected in MGPS2 data [30]. This demonstrates the capability of the current generation of TeV instruments to discover new SNRs.…”
Section: Supernova Remnantsmentioning
confidence: 79%
“…Their emission or upper limits at other wavelengths is needed to understand these sources. HESS J1912+101 is an extended TeV object first reported by Aharonian et al (2008), and recently, with more sensitive data, was shown to resemble a thick shell-type object (Puehlhofer et al 2015;Gottschall et al 2017;H. E. S. S. Collaboration et al 2018).…”
Section: Introductionmentioning
confidence: 85%
“…The shape is slightly elliptical with an extent of approximately 50 ′ × 58 ′ . HESS J1912+101 was tentatively interpreted as an old SNR (Puehlhofer et al 2015;Gottschall et al 2017;H. E. S. S. Collaboration et al 2018), although this interpretation remains inconclusive because of missing signatures at other wavelengths.…”
Section: Introductionmentioning
confidence: 99%